(x+4)²(x-4)²-(3x+2)²(3x-2)²

来源:学生作业帮助网 编辑:作业帮 时间:2024/08/04 02:38:30
(x+4)²(x-4)²-(3x+2)²(3x-2)²
x)Ө6TS64֨Ѕ1u5+`0MR>z lȳi{mt- *LMX(lb0k*@-kz6oγ_,_l+u zcB:f)$AhLSj|1b:AR 9V$TsT\%LE) PC|mc إp\Yj#)Aօ ֣`ah\T-8aj@ (DKzڿ Og/m8i'{'?ml~hg74! *

(x+4)²(x-4)²-(3x+2)²(3x-2)²
(x+4)²(x-4)²-(3x+2)²(3x-2)²

(x+4)²(x-4)²-(3x+2)²(3x-2)²
原式= -80x^4+40x^2+240
= -40(x^2-2)(2x^2+3) ,
如果是解方程,结果为 x=±√2 .

(x+4)²(x-4)²-(3x+2)²(3x-2)²
=[(x+4)(x-4)]²-[(3x+2)(3x-2)]²
=[x²-16]²-[9x²-4]²
= -40(x²-2)(2x²+3)

(x+4)²(x-4)²-(3x+2)²(3x-2)²
=(x²-16)²-(9x²-4)²
=(x²-16+9x²-4)(x²-16-9x²+4)
=(10x²-20)(-8x²-12)
=-40(x²-2)(2x²+3)
以上只是因式分解,具体做法要看题目要求。